Changing maladaptive memories through reconsolidation: A role for sleep in psychotherapy?. (2015) - Diekelmann, Susanne; Forcato, Cecilia
Abstract: Like Lane et al., we believe that change in psychotherapy comes about by updating dysfunctional memories with new adaptive experiences. We suggest that sleep is essential to (re-)consolidate such corrective experiences. Sleep is well-known to strengthen and integrate new memories into pre-existing networks. Targeted sleep interventions might be promising tools to boost this process and thereby increase therapy effectiveness.